2005
DOI: 10.1080/07408170500232297
|View full text |Cite
|
Sign up to set email alerts
|

Run-length distributions ofQ-chart schemes

Abstract: This article studies the performance of the Shewhart chart of Q statistics in the detection of process mean shifts in start-up processes and short runs. We propose an accurate, analytic approximation of this chart's run-length distribution. Our study reveals that the chart has an early detection advantage in that it is more likely than other methods to detect a process mean shift within the first few observations following the shift. This is a desirable property because early detection should make it easier to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In this article, v is assumed to be fixed, but several different values of v are considered in our numerical studies. PROOF: Follows immediately from Brown et al [2] and Appendix B of Zantek [25].…”
Section: Definition: the Recursive Residuals Arementioning
confidence: 82%
See 3 more Smart Citations
“…In this article, v is assumed to be fixed, but several different values of v are considered in our numerical studies. PROOF: Follows immediately from Brown et al [2] and Appendix B of Zantek [25].…”
Section: Definition: the Recursive Residuals Arementioning
confidence: 82%
“…Zantek [25] also gives approximate expressions for the probabilities of RLs greater than one, but he finds cases where they appear to understate the true probabilities by a few percentage points (and in percentage terms by more than 10%). In addition, the accuracy of his expressions is not known for all cases.…”
Section: The Run-length Distributionmentioning
confidence: 96%
See 2 more Smart Citations
“…Quesenberry 7,8 has defined a set of sequential Q statistics to be used in Shewhart, EWMA and CUSUM charts for the detection of changes in the process mean or variance. Del Castillo and Montgomery 9 and Zantek 10 have investigated the statistical properties of Q charts and proposed some enhancements. He et al 11 have demonstrated that the Q charts with unknown variances are biased: that is, for some specific shift mean sizes the Q charts have a larger out-of-control average run length than the expected number of false alarms.…”
Section: Introductionmentioning
confidence: 99%